Parenteral preparations for administration in the pediatric population: The challenges of excipients selection - Krajišnik, Danina (Archives of Pharmacy, 2025)
The need for the development of age-appropriate preparations for patients under 18 years of age is important to ensure appropriate therapy for all children via different routes of administration. Parenteral administration of medicinal products in the pediatric population is common in hospitalized patients, in emergency situations or when the (per)oral route of administration is not possible. The development of a drug formulation for parenteral administration in children requires the consideration of the route of administration (related to physiological differences between children and adults), the site of action and the duration of the pharmacological action of the active substance, the volume of the preparation and the general health condition of the patient. A major challenge in the formulation of these preparations is the selection of excipients that should ensure adequate product quality and patient tolerability.The paper presents an overview of considerations related to the formulation of parenteral preparations for the pediatric population. The regulatory requirements regarding the use of excipients with confirmed effects and the labeling of preparations containing them are listed. Also, modern approaches (databases and tools) that can be useful for the selection of appropriate excipients were considered.